KATA DAN MAKNA: TELAAH SOSIOLINGUSTIK DAN SIMANTIK - Rohman, Fathur (Al Tadib : Jurnal Ilmu Pendidikan, 2017)
The word is a sound formula that is used by humans to designate something by humans, then the sound formula used by humans to communicate between communities. Can not explain the meaning of the whole notion of a word and can not represent the definition of the word itself. Words will always experience growth and change, as well as the meaning of a word will continue to undergo changes and developments in line with the needs of man in his day. The word we mean here is the material equivalent or sound formula for meaning. If we call meaning abstract understanding of the mind that does not refer to the matter (object), then we mean by the word is equivalent mind that according to the understanding of the abstract. So, the word is a form of sound uttered by a person and in accordance with the meaning. The word can also be defined as a tool to show and reveal the contents of the mind. The word is also a tool to show the meaning.